The Zariski topology on the graded primary spectrum of a graded module over a graded commutative ring - Saif Salam; Khaldoun Al-Zoubi (Applied General Topology, 2022)
Let R be a G-graded ring and M be a G-graded R-module. We define the graded primary spectrum of M, denoted by PSG(M), to be the set of all graded primary submodules Q of M such that (GrM(Q) :RM) = Gr((Q:RM)). In this paper, we define a topology on PSG(M) having the Zariski topology on the graded prime spectrum SpecG(M) as a subspace topology, and investigate several topological properties of this topological space.